The effectiveness of the stem kid module for high and moderate achievers elementary school children towards scientific literacy - Nurazidawati Mohamad Arsad; Kamisah Osman; Marlissa Omar; Nur Suhaidah Sukor (International Conference on Research in Education and Science, 2023)
The aim of this research is to determine the effectiveness of the 'STEM Kid Module on the scientific literacy of fifth-grade students in the 'Energy' topic. The module was developed based on the combination of constructivism and constructionism as a fundamental learning theory. Meanwhile, the STEM Kid instructional phase was formed using a STEM integrated approach that included engineering design processes and inquiry-based science learning. A quasi-experimental design was used to assess the effectiveness of the STEM Kid Module. This study included 116 children, 61 of whom were high achievers and 55 of whom were moderate achievers. Two elementary schools using the STEM Kid Module were selected as the treatment group, while another school using conventional teaching approach as the control group. Data for this study were gathered by a scientific literacy test that included scientific knowledge, Science process skills, and daily science application. Results from repeated measurements MANOVA analysis revealed a significant difference in scientific knowledge and daily science application between groups. The study's implication was that the use of the STEM Kid Module through a STEM integrated approach can be implemented in elementary school science teaching and learning for children of varying levels of achievement.